Detained and Denied: the clinical care of immigration detainees living with HIV - Jon Burnett (Medical Justice, 2011)
This report presents the findings of an investigation into the clinical care of immigration detainees living with HIV in the UK, examining the cases of 35 people detained for immigration purposes in an eighteen-month period.